Effects of dam operation on stability, species interactions, and the mechanisms underlying the synchrony of fish in reservoirs. - Baumgartner, Matheus Tenório (2020)
The construction of dams is among the main anthropogenic impacts in natural freshwater systems. The first consequence of impoundments is the formation of reservoirs upstream, which represents a completely new environment compared to the natural river. In addition to this primary impact, the variations in the reservoir water level may be considered another facet of disturbances. Although several studies investigated the processes that occur in reservoirs, there is a shortfall regarding the effects of the dam operation scheme on ecosystem health. Most dams are designed to operate under two almost contrasting schemes: storage (STR) and run-of-river (ROR). These alternative operation schemes result in very different temporal variations, with STR reservoirs presenting rapid fluctuations while ROR reservoirs have a relatively constant volume. Likewise, this difference in the temporal dynamics of water level likely affects the stability of these ecosystems. In order to investigate how the dam operation scheme could affect the temporal stability of freshwater ecosystems, we used the fish communities from two reservoirs in the Iguaçu River that operate under contrasting schemes. The hypothesis was that the STR reservoir would be less stable, considering the environmental heterogeneity created by frequent water level variations, and the interactions among species would be less important for the structure of the resident fish community. In the first approach, the focus was on stability in terms of the ability to resist and recover (i.e., resistance and resilience) to disturbances. In the second approach, empirical data and simulations were used to assess which mechanism (species interactions, environmental or demographic stochasticity) underlie the synchrony of fish communities. Contrary to the expectation, the results showed the ROR reservoir as less stable than the STR, and the mechanisms underlying species synchrony coincided between reservoirs but played opposite roles. More specifically, the temporal dynamics imposed by ROR operation may have weakened the species-environment relationships, which led to a less stable community. Although the results were consistent, they were only primary evidence and such cause-effect relationships between dam operation and its effects on ecosystem stability require further investigations.